Lessons for South Africa: China during the era of ‘reform and opening up’ - Scott, Douglas Ian (New Agenda: SA Journal of Social and Economic Policy, 2024)
China’s four decades of spectacular economic growth may now be slowing down, but the lessons for South Africa – with its own development challenges – remain important. DOUGLAS IAN SCOTT argues South Africa should re-orientate its relationship with China so as to learn from, and recreate, the successes of China’s “reform and opening up” era.